What Health Information is Needed to Improve the Vaccination Outcomes of COVID-19? : Study Analysis in COVID-19 Vaccination in Sangihe Island Regency, Indonesia - Dhito Dwi Pramardika; Jelita Sisika Herlina Hinonaung; Grace Angel Wuaten; Astri Juwita Mahihody (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
The Indonesian government enforces a COVID-19 vaccination policy for all, but the achievement rate for the COVID-19 vaccination in Sangihe Islands Regency at the first dose is only 1.05%, while the achievement at the second dose to date is only 0.47%. With this in mind, the vaccination policy has not been in line with community participation. The purpose of this study was to find out what kind of health information is needed to increase the covid-19 vaccination rate. The method used in this research is a descriptive study with a purposive sampling technique which was held from 7 January to 8 February 2021 with a total sample of 85 respondents who are health workers in the Sangihe Islands Regency. The data analysis used is descriptive analysis with frequency distribution. The results in this study were 15.3% stated that they were not willing to vaccinate COVID-19 because 39% of COVID-19 survivors, 38% had comorbidities, 15% were unsure of safety and 8% feared side effects. The conclusion of this study is to increase health information regarding vaccines for COVID-19 survivors, information about comorbidities such as what is appropriate for COVID-19 vaccination, safety, and side effects resulting from the COVID-19 vaccine.